Pengaruh Perubahan Organisasi Dan Budaya Organisasi Terhadap Kinerja Pegawai (Studi Pada Kantor Pelayanan Kekayaan Negara dan Lelang Banjarmasin) - Ramli Simbolon; Hastin Umi Anisah (JWM (JURNAL WAWASAN MANAJEMEN), 2013)
This study aims to determine and analyze the influence of organizational change and organizational culture either partially or simultaneously to the performance of employees KPKNL Banjarmasin. The population in this study as many as 32 people by using multiple regression analysis method. Analysis regression performed to determine wheter the independent variable (organizational change and organizational culture) either partially or simultaneously influence the dependent variable (employees performance). The result on the State Property Office and Auction (KPKNL) indicate that the change organizations Banjarmasin and cultural organizations simultaneously have a significant and positive impact on employee performance KPKNL Banjarmasin. The result show that partial organizational and cultural changes organizational each have a significant and positive impact on employee performance. Variable factors in the physical arrangement of organizational change to be the most dominant factor affecting the performance of an employee while the factors of attention to detail on the cultural variables are the most dominant factor affecting employee performance.